2020
DOI: 10.1002/app.49773
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(hexamethylene terephthalate/hexamethylene oxamide) alternating copolyamide (alt‐PA6T/62)

Abstract: As a representative polyoxamide, poly(hexamethylene oxamide) (PA62) has good comprehensive performance. However, the high T m (330 C) creates an obstacle for processing. To improve the processability of PA62, poly(hexamethylene terephthalate/hexamethylene oxamide) alternating copolyamide (alt-PA6T/62) was synthesized by hexamethylene diamine-terminated 6T6-diamine and dibutyl oxalate via solution/solid state polycondensation. Random copolyamide (ran-PA6T/62) was also synthesized for comparison. The structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The unique double hydrogen bonding endows it excellent performance, [22][23][24][25] such as high heat resistance, low water absorption, good crystallization properties together with mechanical properties. With the increasing demand for high temperature resistant polyamides in recent years, polyoxamides have aroused more and more attention in industry [26][27][28][29][30][31][32] and academia [33][34][35] and have a good marketing prospects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unique double hydrogen bonding endows it excellent performance, [22][23][24][25] such as high heat resistance, low water absorption, good crystallization properties together with mechanical properties. With the increasing demand for high temperature resistant polyamides in recent years, polyoxamides have aroused more and more attention in industry [26][27][28][29][30][31][32] and academia [33][34][35] and have a good marketing prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has further been reported that the relative insolubility of most polyoxamides prevents the formation of high molecular weight polymers when using conventional solution techniques. To obtain high molecular weight polyoxamides, a two stage procedure has been reported recently, [33][34][35] where a prepolymer is prepared at low temperature from a diester of oxalic acid and a diamine followed by solid state polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the configuration arrangement of the polyamide monomers greatly influenced the physical properties of the derived polymer. Random copolyamides often exhibit relatively low thermal properties and poor mechanical properties because the various irregular arrangements in the polymers undermine the regulated order of the molecular chain and limit the formation of inter- or intramolecular hydrogen bonds in the chains. , In contrast, alternating copolyamides often exhibit more excellent thermal properties, relatively low water absorption, and associated crystallization behavior because they have a more regular molecular chain arrangement . However, the polymerization process for the preparation of complete alternating copolyamides is difficult, uneconomical, and not easy to control …”
Section: Introductionmentioning
confidence: 99%
“…The utilization of BAHT-AA comonomer with PA66 salt as a major monomer for the synthesis of semiaromatic copolyamides has not been mentioned in the literature yet. In this current work, based on our previous reports, the semiaromatic diamine of BAHT has been successfully synthesized by the aminolysis reaction between PET waste and hexamethylenediamine (HMDA), ,,− which is deployed in the modification and synthesis of polyamides. Furthermore, the difference between the PA66/6T polyamides obtained by the conventional synthesis method and the PA66 copolyamides obtained by our method are systematically discussed under the same chemical structure composition and are compared with thermal analysis, wide-angle X-ray diffraction (WAXD), mechanical performance, crystallization kinetics, as well as relaxation and rheological behavior.…”
Section: Introductionmentioning
confidence: 99%